(untitled) (Ustozlar uchun, 2025)
This article examines how additional learning resources support the development of learners’ abilities in English as a Foreign Language (EFL) classrooms. It highlights the pedagogical benefits of integrating extra materials such as documentaries, language-learning websites, graded readers, and mobile applications. The paper explains how these tools reinforce linguistic accuracy, boost student engagement, and promote independent learning. Strategies for adapting extra sources to learners’ proficiency levels are discussed, along with challenges instructors may face. The study concludes that using external resources creates a richer learning environment and contributes to well-rounded language competence.